Power system dynamics and stability - Machowski, Jan.; Bialek, Janusz W.; Bumby, James R. (Chichester ; New York : John Wiley and Sons, 1997)
This book is about: Power system components; The power system in the steady-state; Electromagnetic phenomena; Electromechanical dynamics- small disturbances...
Keywords: Electric power; Electric; Electric power systems; Electric power system stability